Management of a Ruptured Pseudoaneurysm of Common Hepatic Artery Following Pancreaticoduodenectomy - M. Abu-Hilal; M. J. Hallam; B. A. Zeidan; N. W. Pearce (The Scientific World Journal)
Postoperative pseudoaneurysm formation is one of the most feared complications of pancreatic leak following pancreaticoduodenectomy (PD). Surgical repair may be compromised due to a persistent enzymatic insult on the repaired vessel; therefore, preventive measures should be adopted. We report a case of ruptured hepatic artery pseudoaneurysm occurring 12 days following PD in a patient with a postoperative pancreatic fistula. Emergency surgery revealed that the pseudoaneurysm was situated at the point of surgical transfixation of the gastroduodenal artery. The pseudoaneurysm was successfully managed by under-running of the bleeding point combined with the direct application of hemostatic products to the bleeding surface (TachoSilTM and TisseelTM to act as a barrier from the pancreatic secretions.